Preface: pancreas adenocarcinoma - O’Reilly, Eileen M.; Zheng, Lei (Chinese Clinical Oncology, 2017)
Pancreas adenocarcinoma remains a very challenging malignancy with a rising incidence globally and in particular in western countries such as the United States, and China.